The interaction between skeletal muscle mass and visceral adipose tissue in association with inflammatory- and metabolic biomarkers - Jakobsen, Rasmus Dahl (UiT Norges arktiske universitet, 2022)
Obesity has become a global health issue and visceral obesity are associated with several lifestyle diseases. Muscle tissue are known to have anti-inflammatory effects, but how the muscle tissue influences the negative association between visceral obesity and inflammatory- and metabolic biomarkers are a not known. The present thesis aims to investigate the association between different body compositions and inflammatory- and metabolic biomarkers. Data from the seventh Tromsø study were used, and multiple linear regression models were used to portray the association. Higher levels of muscle tissue were only associated with lower levels of HbA1c % in the groups with the highest level of visceral adipose tissue. Visceral adipose tissue was associated strongest with serum CRP and serum triglycerides levels, compared with muscle mass. This indicates that the level of muscle mass is not associated with serum CRP and serum triglycerides but may have a protective effect on HbA1c levels in individuals with a high level of visceral adipose tissue. However, more research is needed to map the total extent of the interaction between body composition and inflammatory- and metabolic biomarkers.